EFFECT ON REVENUE AND EXPENDITURE ECONOMIC GROWTH, POVERTY AND UNEMPLOYMENT (Studies in Budget 2005-2009) - Mansur, Muhammad (Entrepreneur, 2011)
AbstractAPBN is the budget of country every period that describes government’s capability and authority conducting the function of administration to reach the purpose of country.The purpose of this research is to examine the effect of revenue toward economy growth, the effect of expense toward economy growth, the effect of revenue toward poverty, the effect of expense toward poverty and the effect of revenue toward unemployment, the effect of expense toward unemployment. Sample of this research is APBN and realization of APBN from 2005 up to 2009. The same year also prevails for the level of economy growth, poverty, and unemployment. The period of this research is 2005-2009. The method applied in this study is the simple linier regression analysis by using SPSS program 17.0 version for windows. The result of this research shows that revenue does not have significant effect toward economy growth, expense does not have significant effect toward economy growth, revenue has significant effect toward poverty, expense has significant effect toward poverty, revenue does not have significant effect toward unemployment, and expense does not have significant effect toward unemployment.Keywords : revenue, expense, economic growth, poverty, unemploymentAbstrakAPBN adalah anggaran negara setiap periode yang menggambarkan kemampuan pemerintah dan otoritas pelaksana fungsi pemerintahan untuk mencapai tujuan negara. Tujuan dari penelitian ini adalah untuk menguji pengaruh pendapatan terhadap pertumbuhan ekonomi, efek beban terhadap pertumbuhan ekonomi, pengaruh pendapatan terhadap kemiskinan, pengaruh beban terhadap kemiskinan dan pengaruh pendapatan terhadap pengangguran, pengaruh beban terhadap pengangguran. Sampel penelitian ini adalah APBN dan realisasi APBN tahun 2005 sampai 2009. Pada tahun yang sama juga berlaku untuk tingkat pertumbuhan ekonomi, kemiskinan, dan pengangguran. Periode penelitian ini adalah 2005-2009. Metode yang digunakan dalam penelitian ini adalah analisis regresi linier sederhana dengan menggunakan program SPSS versi 17,0 for windows. Hasil penelitian menunjukkan bahwa pendapatan tidak berpengaruh signifikan terhadap pertumbuhan ekonomi, beban tidak berpengaruh signifikan terhadap pertumbuhan ekonomi, pendapatan berpengaruh signifikan terhadap kemiskinan, beban berpengaruh signifikan terhadap kemiskinan, pendapatan tidak berpengaruh signifikan terhadap pengangguran, dan biaya tidak berpengaruh signifikan terhadap pengangguran.Kata kunci: pendapatan, pengeluaran, pertumbuhan ekonomi, kemiskinan, pengangguran